Об определении правой части линейного уравнения колебаний упругой пластины - Гулиев, Г.Ф.; Сейфуллаева, Х.И. (Проблемы управления и информатики, 2017)
Розглянуто обернену задачу з визначення правої частини лінійного рівняння коливань пружної пластини. Задачу зведено до задачі оптимального керування, досліджено функціональну диференційовність і отримано необхідні і достатні умови оптимальності. The inverse problem of determining the right part of linear equation of elastic plate vibration is considered. The problem is reduced to the problem of optimal control, the differentiallity of the functional is studied, necessary and sufficient optimality conditions are obtained.